Influence of the combined system FPS isolator with viscous fluid damper on the dynamic response of the isolated bridges - Kaab, Mohamed-Zohaïr; Ounis, Abdelhafid (Journal of Applied Engineering Science & Technology, 2017)
To illustrate the effect of the combined system FPS isolator (Fiction Pendulum System) with viscous fluid damper on the seismic response of the isolated bridges, a comparative study was realised on a bridge in three different situations. In first situation, we consider the bridge without seismic isolation, while in the second and the third situation, the bridge is successively equipped with a system of FPS isolator then with a combined system FPS isolator and viscous fluid damper. The analysis was done using the digital program of dynamic analysis of the structures SAP2000 and this study consists in comparing the responses of the bridge in terms of baseshear, displacement, acceleration and absorbed energy. The results show that the incorporation of a damping device with viscous fluid damper to the isolator allows to dissipate the maximum of energy, to control the deformations which are located at the level of the isolator and to realize a satisfying compromise between the reduction of the seismic forces and the increase of the deformations in the seismic isolation.